Identification and characterisation of tobacco microRNA transcriptome using high‐throughput sequencing. (21st January 2015) - Gao, J.; Yin, F.; Liu, M.; Luo, M.; Qin, C.; Yang, A.; Yang, S.; Zhang, Z.; Shen, Y.; Lin, H.; Pan, G.; Mock, H.‐P.
Abstract MicroRNAs (miRNAs) are post‐transcriptional regulators that are involved in numerous biological processes in plants. In this study, we investigate miRNAs in Honghua Dajinyuan, an agronomically important species of tobacco in China. Here, we report a comprehensive analysis of miRNA expression profiles in the leaf, stem and root using a high‐throughput sequencing approach. A total of 165 miRNAs, representing 55 conserved families, and 50 novel miRNAs, representing 19 families, were identified in three libraries. In addition, 12 miRNAs were randomly selected from a differentially expressed conserved miRNA family in three libraries with expression alterations and subjected to qRT‐PCR validation. Of these, the expression level of nta‐miR167d is highly enriched in the leaf tissue. In addition, the expression level of nta‐miR319a is prominently enriched in the stem, while nta‐miR160c is highly enriched in the root. Moreover, the target prediction showed that most of the targets coded for transcription factors that are involved in cellular and metabolic processes. GO analysis showed that most of the targets were involved in organelle function, served binding functions, and take part in cellular and metabolic processes. This study helps shed new light on understanding the role of miRNAs in different parts of the tobacco plant and adds a significant number of novel miRNAs to the tobacco miRNA transcriptome.